Sacral character of metals in turkic and kazakh shamanism and healing traditions (Journal of Philosophy Culture and Political Science, 2018)
The article is a cultural interpretation of the traditional knowledge of the sacred Kazakh metals properties within analysis «supernatural», character of iron, copper and plumbum in the Turkic shamanism. In domestic humanities there is a certain reserve devoted to ancient metallurgy and some metals (mainly gold and silver), which is dominated by research in the field of archeology and art. However, there weren’t studies yet on other metals, in current perceptions of traditional and modern Kazakh culture and have not so much an art as a practical healing value.Key words: Kazakh’s culture, Shamanism, semantics, metals, iron, copper, plumbum, traditional healing.